Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1088/1742-6596/1349/1/012094
|View full text |Cite
|
Sign up to set email alerts
|

Melt flow index of low-density polyethylene determination based on molecular weight and branching properties

Abstract: Industrially, a low-density polyethylene (LDPE) is characterized based on their Melt Flow Index (MFI). In numerous publication, LDPE’s MFI is correlated to its average molecular weight (Mw). An overview of modeling studies on LDPE reactors available in the open literature indicates significant discrepancies among researchers for the correlation of MFI-Mw, therefore a research to produce reliable correlation need to be carried out. This research gathers various experimental and industrial data of different LDPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…The energy balance for the reaction and cooling zones are represented by Equations (19) and (20), respectively [7].…”
Section: Peroxide Initiationmentioning
confidence: 99%
See 3 more Smart Citations
“…The energy balance for the reaction and cooling zones are represented by Equations (19) and (20), respectively [7].…”
Section: Peroxide Initiationmentioning
confidence: 99%
“…Equations (37) -(39) represent the calculations for monomer conversion (XM), weightaverage molecular weight (MW) [8] and melt flow index (MFI) [20].…”
Section: Production Outputmentioning
confidence: 99%
See 2 more Smart Citations
“…The material used was Respol LDPE, Alcudia 1970C, with a melt flow index of 7.5 g/10 mins equating to a molecular weight of ~7 × 10 4 Daltons. [3]. Differential scanning calorimetry measurements showed that the onset of crystallization in LDPE happens at 94.2 • C with a maximum rate of crystallization observed at 90.2 • C. These measurements relate to the quiescent melt and the values may be modified by the flow processes inherent in extrusion.…”
mentioning
confidence: 96%